Traffic accident experience and subjective well-being - Daniela Andrén; Erik Johansson Tapper (Örebro University School of Business, 2022)
In this paper we aim to use a posteriori approach to estimate the monetary compensation that would keep the individual's subjective well-being unchanged after experiencing traffic accidents. The coefficients of the life satisfaction equation, estimated with Swedish data collected in May 2020, indicated no statistically significant association between accident experience and life satisfaction. This result is in line with the extensive empirical research on hedonic adaptation that suggests individuals' tendency to adapt relatively fast to new life circumstances and highlights the importance of knowing the time of the accident in order to draw conclusions about when and what monetary compensation might be needed to keep the individuals' life satisfaction unchanged when experiencing, directly or indirectly, a traffic accident.
Keywords: D46; D62; I31; R41; 330; subjective well-being; life satisfaction; well-being valuation method; traffic accident; direct and indirect experience